Risk Analysis of Projects Accordance with the Professional Project Management System: A case- Study Mansur Construction Contracting Company here - نعمة نغم حسين; علي سلوى صالح (Journal of Economics and Administrative Sciences, 2017)
The research aims to identify the risks faced by projects and work on the administration, such as those risks by using professional Project Management System (Project Management Professional) by identifying those risks and their impact on the objectives of the project, if they occur and to provide appropriate responses to Ha.autam search application on the draft Law Faculty port by the General Mansour Construction Contracting company has been using a method personal interview with the heads of departments and project managers in the Al-Mansour and tools descriptive and quantitative analysis as was used (likelihood and impact of risk analysis, Ai_kaoa scheme Sbb- effect, analysis of probability and impact, risk matrix (probability and impact), analysis decision tree) has been collecting information on the theoretical side of the books, research, messaging and Alatarih as well as publications in both Arabic and English versions PMBOK issued by the American Institute PMI, and research found to the high amount of risk in the projects (sample) implemented by the company and the reason for this is the lack of hand specialist risk management or risk management plans as a result of lack of awareness by the management and staff of the importance and impact of the risk and its role in the success of the projects, and research found that if the application of professional projects and requirements management in terms of availability of qualified human resources and technology needed to be applied with respect to the management of risk, he would work to reduce a large proportion of the risks and to provide the appropriate response for the remainder of the risks and would lead to the completion of the projects identified time and cost and to achieve the goals of the company.